Amyloidogenicity of naturally occurring full‐length animal IAPP variants. (23rd June 2019) - Palato, Larry M.; Pilcher, Shannon; Oakes, Alissa; Lamba, Arleen; Torres, Jaris; Ledesma Monjaraz, Litza I.; Munoz, Crystabel; Njoo, Edward; Rinauro, Dillon J.; Menefee, Kate Alexandra; Tun, Angela; Jauregui, Betssy L.; et al.
Abstract : The aggregation of the 37‐amino acid polypeptide human islet amyloid polypeptide (hIAPP), as either insoluble amyloid or as small oligomers, appears to play a direct role in the death of human pancreatic β‐islet cells in type 2 diabetes. hIAPP is considered to be one of the most amyloidogenic proteins known. The quick aggregation of hIAPP leads to the formation of toxic species, such as oligomers and fibers, that damage mammalian cells (both human and rat pancreatic cells). Whether this toxicity is necessary for the progression of type 2 diabetes or merely a side effect of the disease remains unclear. If hIAPP aggregation into toxic amyloid is on‐path for developing type 2 diabetes in humans, islet amyloid polypeptide (IAPP) aggregation would likely need to play a similar role within other organisms known to develop the disease. In this work, we compared the aggregation potential and cellular toxicity of full‐length IAPP from several diabetic and nondiabetic organisms whose aggregation propensities had not yet been determined for full‐length IAPP. Abstract : The aggregation of the pancreatic peptide, islet amyloid polypeptide (IAPP), into toxic amyloid appears to play a role in β‐cell death and the progression of type 2 diabetes. Naturally occurring variants of IAPP from diabetic and nondiabetic organisms were characterized for their ability to aggregate into amyloidogenic species.